Clinical Identification and Management of Hypertension in a Primary Care Setting at Segala Mider Public Health Center - Nita Sahara; Destriana Hasan; A Fatwa Alwaliu; Achmad Farhan; Adelia Putri Sardi; Adis Adelia; Ady Wahyu Pratama (CV. FOUNDAE, 2025)
Hypertension remains a major global health challenge and a leading contributor to cardiovascular morbidity and mortality. Its asymptomatic nature causes many individuals to remain undiagnosed, increasing the risk of severe complications such as stroke, coronary artery disease, and renal impairment. Despite advancements in diagnostic and therapeutic approaches, hypertension awareness and treatment adherence remain low, particularly in primary care settings where early detection is crucial. This study describes the clinical identification and management process of a hypertensive adult patient at Segala Mider Public Health Center as an illustration of the essential role of primary healthcare services in improving hypertension control at the community level. Clinical data were collected through patient interviews, vital sign assessment, physical examination, and review of medical records. The patient, a 42-year-old male, presented with recurrent dizziness triggered by physical activity and consumption of sweet foods. Initial evaluation showed severely elevated blood pressure at 164/122 mmHg with otherwise normal cardiopulmonary findings. The patient had previously been taking amlodipine 5 mg daily with suboptimal response. Management involved titration of amlodipine to 10 mg daily for 15 days, accompanied by short-term furosemide therapy and vitamin B complex supplementation. The intervention produced symptomatic improvement and facilitated better blood pressure control during follow-up. The findings highlight the importance of timely recognition of uncontrolled hypertension, appropriate pharmacological adjustment, and continuous monitoring. This report emphasizes the relevance of primary care in initiating evidence-based treatment, identifying modifiable risk factors, and ensuring patient education regarding lifestyle modification. The novelty of this study lies in demonstrating how structured evaluation and treatment optimization in a resource-limited primary care setting can effectively support hypertension control while preventing long-term complications, reinforcing the vital role of frontline healthcare facilities in managing chronic diseases.